2010
DOI: 10.1364/oe.18.019367
|View full text |Cite
|
Sign up to set email alerts
|

Generalized sampling using a compound-eye imaging system for multi-dimensional object acquisition

Abstract: Abstract:In this paper, we propose generalized sampling approaches for measuring a multi-dimensional object using a compact compound-eye imaging system called thin observation module by bound optics (TOMBO). This paper shows the proposed system model, physical examples, and simulations to verify TOMBO imaging using generalized sampling. In the system, an object is sheared and multiplied by a weight distribution with physical coding, and the coded optical signal is integrated on to a detector array. A numerical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 24 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…11 This section shows the implementations of the coding scheme for the applications. Those applications can be combined for multidimensional imaging.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 This section shows the implementations of the coding scheme for the applications. Those applications can be combined for multidimensional imaging.…”
Section: Applicationsmentioning
confidence: 99%
“…[5][6][7][8][9][10] We have proposed a generalized framework to acquire multidimensional optical data with a compound-eye imaging system named thin observation by bound optics (TOMBO). 11 The framework realizes multidimensional imaging with a compact hardware. This proceeding shows the concept briefly and its applications.…”
Section: Introductionmentioning
confidence: 99%
“…Compressive imaging (CI) techniques were developed for various purposes, such as reducing hardware requirements [3][4][5], shortening image scanning times [3,6], increasing resolution [7][8][9][10], motion tracking [11,12], imaging through partial occlusion [13], imaging with a single bit sensor [14], and improving other imaging performances [15]. A review of CI techniques may be found in [16].…”
Section: Introductionmentioning
confidence: 99%
“…Through the imaging of each microlens on the photo-detector, a wide field of view (FOV) detection can be realized. Recently, some miniaturized imaging systems based on artificial compound-eye have been proposed, such as an artificial apposition compound-eye imaging system designed based on the opposition compound eyes of small invertebrates [6], thin observation module by Bound Optics TOMBO [7], and reconstruction methods based on interpolation of pixel values [8]. The methods can be used in detection with large area, but imaging with the wider FOV has been limited by the planar microlens array of the system.…”
Section: Introductionmentioning
confidence: 99%